Antimicrobial resistance of Streptococcus pneumoniae recovered from outpatients in the United States during the winter months of 1994 to 1995: results of a 30-center national surveillance study. - Doern, G; Brueggemann, A; Holley, H; Rauch, A (1996)
A total of 1,527 clinically significant outpatient isolates of Streptococcus pneumoniae were prospectively collected in 30 different U.S. medical centers between November 1994 and April 1995. Overall, 23.6% of strains were not susceptible to penicillin, with 14.1% intermediate and 9.5% high-level resistant. The frequencies of recovery of intermediate and high-level resistant strains varied considerably between different medical centers and in different geographic areas. In general, intermediate and high-level penicillin resistance was most common with isolates of S. pneumoniae recovered from pediatric patients. The in vitro activities of 22 other antimicrobial agents were assessed against this collection of isolates. Ampicillin was consistently 1 twofold dilution less active than penicillin. Amoxicillin and amoxicillin-clavulanate were essentially equivalent to penicillin in activity. The rank order of activity for cephalosporins was cefotaxime = ceftriaxone > or = cefpodoxime > or = cefuroxime > cefprozil > or = cefixime > cefaclor = loracarbef > cefadroxil = cephalexin. The National Committee for Clinical Laboratory Standards [Performance Standards for Antimicrobial Susceptibility Testing, Sixth Information Supplement (M100-S6), 1995] has established MIC breakpoints for resistance (i.e., > or = 2 micrograms/ml) with three cephalosporins versus S. pneumoniae, namely, cefotaxime, ceftriaxone, and cefuroxime. The overall percentages of strains resistant to these three antimicrobial agents were 3, 5, and 12, respectively. The overall frequency of resistance was 10% with all three macrolides examined in this study, clarithromycin, erythromycin, and azithromycin. The overall percentages of chloramphenicol, tetracycline, and trimethoprim-sulfamethoxazole resistance were 4.3, 7.5, and 18, respectively. The resistance percentages among the cephalosporins, macrolides, chloramphenicol, tetracycline, and trimethoprim-sulfamethoxazole were consistently higher among penicillin-intermediate strains than among susceptible isolates and even higher still among organisms expressing high-level penicillin resistance. Multiply resistant strains represented 9.1% of the organisms examined in this study. Finally, rifampin resistance was uncommon (i.e., 0.5%), and vancomycin resistance was not detected. The quinopristin-dalfopristin combination was consistently active at concentrations of 0.25 to 4 micrograms/ml, but rates of resistance could not be determined in the absence of established interpretive criteria for MIC results.